Family Bonds : Free Blacks and Re-enslavement Law in Antebellum Virginia - Maris-Wolf, Ted (Book collections on Project MUSE., 2015)
Between 1854 and 1864, more than 100 free African Americans in Virginia proposed to enslave themselves and, in some cases, their children. Ted Maris-Wolf explains this phenomenon as a response to state legislation that forced them to make a terrible choice: leave enslaved loved ones behind for freedom elsewhere or seek a way to remain in their communities, even by renouncing legal freedom. Painting an intimate portrait of people whose lives, liberty and use of Virginia law offer new understandings of race and place in the upper South, he shows how they quietly challenged prevailing notions of racial restriction and exclusion, weaving themselves into the social and economic fabric of their neighbourhoods and claiming, through unconventional or counterintuitive means, certain basic rights of residency and family.